Pityriasis Rubra Pilaris refractory to ustekinumab successfully treated with guselkumab - João Teixeira; Ana L. Matos; André Aparício‐Martins; Joana Calvão; Hugo S. deOliveira (Wiley, 2024)
Abstract Pityriasis Rubra Pilaris (PRP) is a rare papulosquamous inflammatory dermatosis with variable clinical presentation and poorly understood pathogenesis that often poses diagnostic and therapeutic challenges. Data on currently available treatment options are limited, particularly when facing refractory cases. Both ustekinumab, an interleukin‐12 (IL‐12) and IL‐23 inhibitor, and guselkumab, an IL‐23p19 inhibitor, target the Th‐17 axis and are well established treatment options in moderate to severe psoriasis. However, increasing evidence, mostly derived from case reports and supported by recent understanding of the role of Th‐17 axis in PRP, also favours the use of IL‐17/IL‐23 pathway inhibitors in this disease. We present an adult female patient with long history of recalcitrant PRP refractory to multiple treatment options. Although initial improvement with ustekinumab was achieved, late disease progression ensued, leading to transition to guselkumab with remarkable clinical response.